Effect of Epoetin Alfa and Sodium Valproate in Patients with Myelodysplastic Syndrome - Hosseini, Seyed Ashkan; Tabarraee, Mahdi; Ghadiani, Mojtaba (Novelty in Biomedicine, 2020)
Background: Myelodysplastic syndrome (MDS) is an important precancerous disease leading to blood malignancies. Prompt diagnosis and treatment would result in better outcome in patients. Purpose of the study was to determine the effect of Epoetin Alfa and Sodium Valproate in patients with MDS. Materials and Methods: In this interventional quasi-experimental study, 50 consecutive patients with MDS from Taleghani Hospital (Tehran, Iran) in 2016-2017 were enrolled. They underwent treatment for eight months with 10000 units per month from Epoetin Alfa plus 200 mg TDS from Sodium Valproate. The hematological response was determined according to the hemoglobin, platelet, and neutrophil. Results: Hematological response was present in 68%. The packed cell treatment were decreased significantly (P=0.040) and 56% of patients had no receipt of packed cells after treatment. Conclusion: It is concluded that Epoetin Alfa plus Sodium Valproate was effective in treatment of patients with Myelodysplastic syndrome and use of this combination therapy is recommended.